The effect of levosimendan on Tp-e interval, Tp-e/QT ratio, Tp-e/QTc ratio and QRS interval in heart failure patients - Aktas, Ibrahim; Karakus, Alper; Camci, Sencer; Ari, Hasan; Ari, Selma; Tutuncu, Ahmet; Melek, Mehmet; Bozat, Tahsin (The European Research Journal, 2017)
Increased Tp-e interval (from the peak-to-the-end of the electrocardiographic T wave) and Tp-e/QT ratio are associated with malignant ventricular arrhythmias. We aimed to evaluate the acute effects of levosimendan on Tp-e interval, Tp-e/QT ratio, Tp-e/QTc ratio and QRS interval in patients with severe heart failure.Methods. The study included 85 patients with decompansed heart failure, who were treated with levosimendan in our cardiology department. We evaluated the patients retrospectively. QT and Tp-e interval were assessed in the precordial leads. QRS duration was determined in the single lead which had the longest QRS. Electrocardiographic measurements was performed the basal (just before the levosimendan) and 24th hour after the levosimendan infusion (just after the levosimendan infusion). Results. No significant differences were found between before and after treatment of levosimendan with respect to Tp-e and QTc interval, QRS duration, Tp-e/QT and Tp-e/QTc ratio (pretreatment versus 24th hour values; p>0.05). Subgroup analysis was performed in the patients with inotropic therapy including dopamine and/or dobutamin (34 patients) and without inotropic therapy (49 patients) during the levosimendan infusion. The analysis showed that pretreatment and 24th hour values of Tp-e interval and Tp-e/QT ratio were significantly higher in the inotropic therapy group; (Pretreatment; Tp-e: 100.12±22.96 milliseconds [ms] versus 89.59±17.67 ms; p=0.03, Tp-e/QT: 0.26±0.05 versus 0.23±0.04; p=0.007, 24th hour: Tp-e: 101.41±27.09 ms versus 88.77±15.89 ms; p=0.009, Tp-e/QT: 0.26±0.07 versus 0.23±0.05; p=0.03). However intra-group changes of these parameters, before and after levosimendan treatment, were not significant (p>0.05).Conclusion. Our results suggested that, therapeutic doses of levosimendan infusion don’t have a significant effect on Tp-e and Tp-e/QT parameters. However inotropic therapy significantly increases these parameters.